Gut Metabolite Trimethylamine-N-Oxide in Atherosclerosis: From Mechanism to Therapy - Wang, BingYu; Qiu, Jun; Lian, JiangFang; Yang, Xi; Zhou, JianQing (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerosis is associated with various pathological manifestations, such as ischemic heart disease, ischemic stroke, and peripheral arterial disease, and remains a leading cause of public health concern. Atherosclerosis is an inflammatory disease characterized by endothelial dysfunction; vascular inflammation; and the deposition of lipids, cholesterol, calcium, and cellular debris within the vessel wall intima. In-depth studies of gut flora in recent years have shown that bacterial translocation and the existence of bacterial active products in blood circulation can affect the inflammatory state of the whole blood vessel. The gut flora is considered to be a large “secretory organ,” which produces trimethylamine-N-oxide (TMAO), short-chain fatty acids and secondary bile acids by breaking down the ingested food. Studies have shown that TMAO is an independent risk factor for the occurrence of malignant adverse cardiovascular events, but whether it is harmful or beneficial to patients with cardiovascular diseases with mild or no clinical manifestations remains controversial. We review the relationship between TMAO and its precursor (L-carnitine) and coronary atherosclerosis and summarize the potential molecular mechanism and therapeutic measures of TMAO on coronary atherosclerosis.